In silico prediction of the pharmacological potential of new 7-alkyl-8-hydrazine derivatives of 1,3-dimethylxanthine - L. M. Mosula; V. S. Mosula; D. B. Korobko (Zaporozhye State Medical University, 2024)
The development of new drug-like molecules based on 7-R-8-hydrazine derivatives of 1,3-dimethylxanthine is promising in view of the known pharmacological effect of theophylline and functional hydrazine derivatives. In silico methods make it possible to rationalize the synthesis and reduce the number of chemical compounds at the stage of virtual screening by eliminating potentially ineffective molecules. The aim of the work was to carry out а virtual design and predictive evaluation of pharmacological activity of new 7-alkyl-8-hydrazine derivatives of 1,3-dimethylxanthine by in silico methods. Materials and methods. To perform in silico prediction of the pharmacological potential of several new 7-alkyl-8-hydrazine derivatives of 1,3-dimethylxanthine, we used the online services. As 12 model compounds, we chose 12 derivatives of 5-(2-(1,3-dimethyl-2,6-dioxo-2,3,6,7-tetrahydro-1H-purin-8-yl)hydrazine)-5-phenylpentanoic acid with linear and branched alkyl substituents at the 7th position of the basic heterocycle: methyl-, ethyl-, n-propyl-, n-butyl, i-butyl, n-amyl, i-amyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl. The use of the freely available web tool SwissADME made it possible to calculate physicochemical parameters and to determine the drug-likeness properties of molecules. And other Internet platforms allowed to predict the spectrum of biological activity of the target compounds. Results. In silico analysis of the pharmacological potential of model compounds was performed. Three biological actions (peripheral vasodilator, kidney function stimulant, lipoprotein lipase inhibitor) with high Pa values are predicted for all derivatives of the series. The ADME parameters of the molecules were evaluated and their potential drug-like properties were determined. Conclusions. It was established that the extension of the alkyl substituent at the 7th position of the basic heterocycle should lead to a deterioration of the ADME parameters of the molecules, potentially reduce their oral bioavailability, but should not radically affect their biological activity profile. Compounds 1-3 and 5 are predicted to be orally bioavailable. They should be characterized by a wide spectrum of biological activity with the highest probability of vasodilator effect on peripheral vessels. In the future, it is advisable to carry out targeted synthesis of hit compounds and thorough in vitro, in vivo studies, and for compounds with violated physicochemical criteria - structural optimization of molecules in order to find a lead compound.